PAI Teachers and the Phenomenon of Spiritual Quiet Quitting: A Study on the Decline of Students' Worship Motivation Amid Academic Curriculum Density - Sesilia Marsya Nabila Zahara; Rice Putri Dia Utami; Muhammad Yasin Abdul Aziz Rantisi Nasution; Lety Febriana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The transformation of academic curricula demanding intensive cross-disciplinary competencies has produced a density of learning agendas with implications for students' psychological and spiritual dimensions. This phenomenon gives rise to a condition conceptualized as "spiritual quiet quitting", a term borrowed from workplace literature describing students who continue to perform worship formally while losing inner engagement, devotion, and meaning. This study aims to conceptually examine the relationship between academic curriculum density and the decline of students' worship motivation, to identify the characteristics of spiritual quiet quitting, and to analyze the role and strategies of Islamic Religious Education (PAI) teachers in responding to it. The study employs a qualitative descriptive-analytical library research approach, drawing data from nationally and internationally indexed journal articles published between 2019 and 2026, analyzed through data reduction, display, and conclusion drawing following the Miles and Huberman model. The findings indicate that, viewed through the job demands-resources framework, curriculum density can function as a demand that depletes students' psychological resources when not balanced by supporting resources such as social support and adequate spiritual meaning-making. PAI teachers hold a crucial role through authentic exemplary conduct, affective-personal approaches grounded in fulfilling the basic psychological needs of autonomy, competence, and relatedness, and reorienting the worship narrative from administrative obligation toward meaningful practice, as a preventive step against the spread of spiritual quiet quitting in school settings. Keywords: PAI teacher; spiritual quiet quitting; worship motivation; curriculum density; academic burnout; self-determination theory